Awareness of listeriosis among Portuguese pregnant women - Mateus, Teresa (2015)
In pregnant women listeriosis may cause abortion, foetal death or neonatal morbidity in the form of septicaemia and meningitis. Improved education concerning the disease, its transmission and prevention measures have been identified as a pressing need. The aim of this study was to evaluate the food safety knowledge and practices among pregnant women in Portugal, giving particular relevance to listeriosis. For this purpose, a written questionnaire was constructed and answered by 956 women. Half of the respondents considered they had received a sufficient amount of information on food safety during pregnancy. This information was mainly provided from their doctors, who were considered the most competent to give this information. Although 32.3% of women interviewed had not changed their habits of preparation and cooking foods after becoming pregnant, the greater the amount of information received the more effective the change of habits was. A significant number of women avoided the consumption of foods considered to be high risk, however, for 32.0% of these women these foods were only avoided in meals taken outside home. The amount of information received influenced the foods avoided. Only 12.2% of the women interviewed had heard about listeriosis and, 47.0% of these did not know about the problems it can cause.Women who have had three or more pregnancies were those that most frequently reported not having received information or having received little information. These women also demonstrated less knowledge about listeriosis. The larger number of pregnancies corresponded with less economic resources and less education of the respondents. Women showed plenty of interest in receiving information about listeriosis; doctors and written information in flyers or in the Pregnancy bulletin provided by the State Medical Service were the main sources of information referred. It appears that planning is required, to raise awareness amongst health professionals of the need for food safety education for pregnant women.